Development and testing of a three-section pulse-forming network and its application to Marx circuit. (2nd December 2019) - Song, Falun; Zhang, Beizhen; Li, Chunxia; Li, Fei; Wang, Ganping; Gong, Haitao; Gan, Yanqing; Jin, Xiao
Abstract: A three-section pulse forming network (PFN) based on Guillemin type-C circuit was developed to meet the challenge of a compact design, high withstand voltage, and high-quality output waveform with fast rise time, flat-top duration, and 100-ns pulse width. A simplified pulse forming circuit was proposed and studied that includes only three LC-sections connected in parallel, with each section containing an inductor and a capacitor connected in series. The effect of the capacitance deviation on the output waveform was investigated. The simulation results show that when the capacitance deviation exceeds +3%, both the flat top and fall time of the output waveform of single PFN module deteriorate greatly. Fortunately, in a multi-stage PFN-Marx circuit, even if the capacitance deviation exceeds +10%, when the average capacitance of the same LC sections is close to the theoretical value, the output waveform maintains a good quality and is in good agreement with the theoretical prediction. The compact three-section PFN developed during this project has a size of only 360 mm × 342 mm × 65 mm, and a maximum withstand voltage of 120 kV. Sixteen PFN stages were assembled to form a Marx generator with design parameters to provide of an output peak power of 12 GW and a maximum peak current of 15 kA. The tested output waveform agrees well with the theoretical results, having a rise time of 31 ns, a flat-top of 104 ns, and a pulse with of 164 ns.